Spontaneous Rupture of Intracranial Dermoid Cyst Mimicking a Primary Psychiatric Disorder - Erol, Fatih Serhat; Ozturk, Sait; Cakin, Hakan; Akin, Mehmet Mustafa (Galenos Yayincilik, 2014)
We discussed the case of a 14-year-old patient with acute onset of psychiatric symptoms for two months who had been examined and different antipsychotic drugs had been prescribed by several psychiatrists without any neuroradiological imaging. Because of unresponsiveness to the antipsychotic drugs, computed tomography and magnetic resonance imaging were performed which revealed a ruptured intracranial dermoid cyst. The patient underwent surgery and antipsychotic medications were withdrawn in short time. The emphasis of this case is that intracranial lesions can present with neuropsychiatric symptoms and findings only without any neurological deficit or signs.
Primer bir psikiyatrik bozuklu?u taklit eden spontan rüptüre İntrakraniyal dermoid kist
Keywords: Dermoid cyst; intracranial tumor; magnetic resonance imaging; psychiatric disorder